Status jaringan periodontal dan kebutuhan perawatan jaringan periodontal pada manula Suku Bugis dan Suku Mandar - Bahruddin Thalib; Dian Angriani (DiscoverSys Inc., 2007)
Being old is a biologic process that can not be avoided, where degeneration occurs inmany ways, which finally decreases the function. These cause aging people prone tovarious diseases; including periodontal disease. Prevalence and severity of periodontaldiseases vary in world population. These differences seem to be related with age, sex,socioeconomic, education, and also ethnic and geography. This study was aimed toinvestigate the periodontal tissue of aging Buginese and Mandarnese. Total samples are390 persons (195 Buginese dan 195 Mandarnese). The condition of periodontal tissuewere checked using CPITN from WHO. Of 195 samples, 88 samples of Buginese and 55samples of Mandarnese were edentulous. The result showed periodontal disease ofBuginese were bleeding 2.8%, tartar 39.25%, pocket of 4-5 mm depth, 50.47%, andpocket of 6 mm depth, 7.48%. Periodontal disease of Mandarnese ethnic were bleeding2.14%, tartar 53.57%, pocket of 4-5 mm depth 21.43%, and pocket of 6 mm depth22.86%. Therefore, the need for periodontal treatment for aging Buginese were brushingteeth instruct 100%, prophylaxis 97.19%, and restorative 7.46%. Aging Mandarnese;were brushing teeth instruction 100%, prophylaxis 97.85%, and restorative 22.86%.